THE THYMUS GLAND IS THE CENTRAL ORGAN OF IMMUNITY AND BLOOD CIRCULATION (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
In the last 20-25 years, there has been a very rapid development of immunology, the cellular and subcellular foundations of the immune response, the participation of the thymus in immunosuppression processes have been clarified. The thymus is the central organ of the immune system, where, under the action of hormones and biologically active substances, the number of which includes more than 30 names, the initial stages of T-lymphopoiesis are carried out, the formed pretimocytes and thymocytes migrate from the thymus to the peripheral organs of immunity and reach their maturity. At the same time, the structural and functional features of the thymus reaction during antigenic stimulation are still poorly understood. In this regard, the purpose of our study was to clarify the cellular and subcellular mechanisms of thymus involvement in immunogenesis in experimental salmonella infection.